Epipelon dynamics in a shallow lake through a turbid-and a clear-water regime - Cano, María Gabriela (2016)
In Pampean lakes, very little information is available on epipelon structure and dynamics or the effect of environmental variables on those parameters. We anticipate that light may have the greatest influence on this community and that the nutrient concentration and substrate instability may exert secondary effects. Our objective was to analyze variations in descriptive parameters and in the algal species composition of the epipelon in the Pampean Lake Lacombe over space and time to establish the most influential environmental forces (light climate, wave action, nutrients). Sediment was collected from the benthos with a 3.5-cm-diameter corer in a year-round sampling every month at four sites in the lake that differed from each other in depth, distance from the shore, and the presence of emergent and submerged macrophytes. Although Lacombe is a shallow lake, differences occurred in community descriptive variables and in the epipelon composition (especially diatoms) over space and time. In particular, differences between the site nearest to the shore and the rest of the sites were found with respect to environmental variables (sediment-particle size, total phosphorus, organic matter content, light climate), epipelon descriptive parameters (abundance, chlorophyll a and Margalef’s index) and epipelon composition (especially specific biovolume and diatom-size classes). The epipelon also reflected, though slightly, the change from the turbid- to clear-water states in the lake. Sediment erosion or deposition was evidenced by differences in the sediment-particle composition and the predominant particle-size classes at each site. Statistical analyses indicated linear correlations between the epipelon parameters and variables related to the light climate in the water column. Conductivity and sediment total phosphorus and density were also correlated, but to a lesser extent, with epipelon composition. The epipelon variations in Lacombe Lake would exemplify the reference communities developed during clear or turbid regimes in Pampean shallow lakes. We found evidence for the influence of light climate and wave action (through instability of the substrate) on this community, but the effect of nutrients was negligible. We emphasize that the close relationships maintained by the epipelon with other communities such as the phytoplankton and the epiphyton may superimpose the patterns of variation to those communities onto the epipelon dynamics.